2014
DOI: 10.1074/jbc.m113.520742
|View full text |Cite
|
Sign up to set email alerts
|

RGS6, but Not RGS4, Is the Dominant Regulator of G Protein Signaling (RGS) Modulator of the Parasympathetic Regulation of Mouse Heart Rate

Abstract: Background: RGS4 and RGS6 are regulator of G protein signaling (RGS) proteins, and both have been proposed to modulate parasympathetic regulation of heart rate (HR). Results: RGS6 ablation enhances parasympathetic influence on the heart; RGS4 ablation does not. Conclusion: RGS6 is the primary RGS modulator of parasympathetic influence on the heart. Significance: Understanding the parasympathetic regulation of HR will improve treatment of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
3
39
2
Order By: Relevance
“…RGS6 acts as a critical negative regulator of M 2 R signalling in the sinoatrial node of the heart rapidly terminating Gβγ signalling and thus curtailing vagal lowering of the heart rate2526. The results of our meta-analysis are consistent with a role for RGS6 in decreasing HRV previously hinted at by animal experimentation2327 and a human case report2728.…”
Section: Discussionsupporting
confidence: 86%
“…RGS6 acts as a critical negative regulator of M 2 R signalling in the sinoatrial node of the heart rapidly terminating Gβγ signalling and thus curtailing vagal lowering of the heart rate2526. The results of our meta-analysis are consistent with a role for RGS6 in decreasing HRV previously hinted at by animal experimentation2327 and a human case report2728.…”
Section: Discussionsupporting
confidence: 86%
“…Structure-function and mutagenesis studies demonstrated that the high Gβγ-dependent component of I basal of GIRK1-containing channels depends on the unique distal CT domain of GIRK1 Kahanovitch et al, 2014;Rubinstein et al, 2009;Wydeven, Fernandez de Velasco, et al, 2014;Wydeven, Posokhova, et al, 2014). Deleting distal CT from GIRK1*, or replacing it with the shorter distal CT of GIRK2a, reduces Gβγ binding to the cytosolic domain of GIRK1, eliminates Gβγ recruitment, and strongly reduces I basal (although not to a level as low as that of GIRK2a).…”
Section: Basal and I Evoked Are Interrelated: The Roles Of Gα Gdp Amentioning
confidence: 94%
“…Considerable GPCR-independent I basal has been reported for GIRK1/4, GIRK1/2, and GIRK1* He et al, 2002;Kahanovitch et al, 2014;Peleg et al, 2002;Rishal et al, 2005;Rubinstein et al, 2007;Wydeven, Fernandez de Velasco, et al, 2014;Wydeven, Posokhova, Xia, Martemyanov, & Wickman, 2014). The involvement of Gβγ in I basal has been studied by coexpressing proteins that are expected to "steal" the available Gβγ from GIRK, termed Gβγ scavengers: C-terminus of β-adrenergic kinase, phosducin (see Rishal et al, 2005), and an "inactive" mutant of Gα i3 , Gα i3-G203A , which strongly binds Gβγ and is deficient in GDP-GTP exchange (Ogier-Denis, Houri, Bauvy, & Codogno, 1996).…”
Section: Heterologous Expression Studies: Gpcr-independent I Basal Anmentioning
confidence: 96%
See 1 more Smart Citation
“…RGS4 and RGS6 are found to regulate the M2 receptor activation-mediated I KACh . 7,8 In addition to M2 receptors, atrial cardiomyocytes also express M3R, and its activation may play a key role in initiation and perpetuation of atrial fibrillation. 9 Therefore, RGS2, a putative regulator of the M3R receptor, may be a target for therapeutic importance.…”
Section: See Related Article Pp 86-98mentioning
confidence: 99%